EFEKTIVITAS PELAYANAN KESEHATAN DARI PERUBAHAN BENTUK PELAYANAN SATUAN KERJA RUMAH SAKIT UMUM DAERAH MENJADI BADAN LAYANAN UMUM DAERAH (STUDI KASUS RSUD SANJIWANI GIANYAR) - Devi Widyaswari, Anak Agung; R., Ibrahim; Dahana, Cokorda Dalem (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
This paper entitled “The Effectiveness Of Service Health By Changing The Service Unit Into General Service District Body (Case Study in Sanjiwani Hospital of Gianyar)”. This paper uses yuridical emperical methods. The paradigm in the state financial sector there is a shift from the traditional estimation, becomes estimation performance based budgeting. One form of performance-based budgeting is BLUD. There are a problems , are RSUD Sanjiwani Gianyar have been applied financial management pattern of the general services district (PPK-BLUD) and how is the implication of PPK-BLUD towards service for society. PPK-BLUD provides flexibility and effiency in the form of discretion in the body business practises to improve service for healthy societies. RSUD Sanjiwani Gianyar have been effective to apply PPK-BLUD.
Keywords: Effectiveness, Service Of Health, Changes In Unit Form, The General Service District Body.